Exploring the pH dependent redox behaviour of polyoxometalates for electrochemical energy storage - Lowe, Grace A. (2019)
The polyoxometalate (POM) H6[P2W18O62] was dissolved in different aqueous electrolytes to make anolytes for redox flow batteries (RFBs). These anolytes were tested in a laboratory-scale RFB with TEMPO and ferrocene-based catholytes. In a separate study, a series of POMs were encapsulated inside single-walled carbon nanotubes (SWNTs) and these redox active materials were studied using voltammetry in high and low pH electrolytes. To make the RFB anolytes, H6[P2W18O62] was dissolved in either 1.0 M H2SO4 aq., or 1.0 M citrate buffer aqueous. These anolytes were combined with different catholytes and membranes in a laboratory-scale RFB which was then tested by charging and discharging the RFB at constant current. A negatively charged TEMPO salt was found to show limited cross-over when use with the cation exchange membrane Nafion-117. The RFB with an acid catholyte lost capacity within the first four charge-discharge cycles. This was due to adsorbed POM on the electrode surface that reacted to form a hydrogen evolution catalyst. Dissolving the same POM in a citrate buffer prevented adsorption of the POM. However, side reactions with the buffer were detected using 31P-NMR of the anolyte and gas chromatography. SWNTs were treated with aqueous solutions of K6[P2W18O62], H3[PW12O40], and K6[P2Mo18O62] to make POM@CNT composites in which most of the POM was encapsulated inside the SWNT. The encapsulation was confirmed by TEM, as well as voltammograms recorded for washed composites. The tungstate POM@CNT composites exhibited enhanced stability in high pH solutions compared to dissolved POM and reversible redox behaviour in low pH electrolytes. The highest specific capacity achieved in this work was 58 mAh g−1. New redox active materials are needed to meet our future energy storage requirements and accelerate the transition to carbon neutral energy generation. POMs encapsulated inside SWNTs formed a new class of material which can reversibly store electrons. Meanwhile, RFBs must store energy at a low cost to energy ratio. The state-of-the-art all vanadium aqueous redox flow batteries are limited by the price and solubility of the vanadium salts. POMs are highly soluble and can store multiple electrons per anion, which allows the energy density of the electrolyte to be increased. Many inexpensive highly soluble organic redox couples have already been developed for aqueous RFB catholytes. In this study model tungstate POM anolytes were combined with a selection of these catholytes to find an optimum combination to develop to increase the energy density of RFBs.